Creatine Phosphate in Rat Platelets Decreased by ADP or Thrombin - Shibata, Sachiko (Thrombosis and Haemostasis, 1979)
ADP or thrombin caused a transient change in creatine phosphate (CP) content of rat platelets. At 25°C the CP content decreased most 30 sec after the addition of ADP or thrombin and recovered thereafter. ATP or AMP was without effect. The rat platelets aggregated at 25° C by ADP or thrombin, but the changes in CP content by these inducers were also observed in the platelet preparations unable to aggregate by the lack of Ca2+. A persistent chilling made the platelets lose their ability to change CP content. It was suggested that in rat platelets CP is consumed in the early stage of the response to the aggregating agents, presumably donating the energy for shape change.